Exploring Clinical and Imaging Differences in COVID-19: an Observational Approach to the IFITM3 rs12252 Polymorphism - Mitrea A; Mitroi AF; Opariuc-Dan C; Constantin AA; Dantes E (International Journal of General Medicine)
Adriana Mitrea,1,2 Anca-Florentina Mitroi,3,4 Cristian Opariuc-Dan,5 Ancuta-Alina Constantin,6,7 Elena Dantes8,9 1Doctoral School of Medicine, “Ovidius” University of Constanta, Constanta, Romania; 2Department of Pulmonology, “Sf. Apostol Andrei” Emergency Clinical County Hospital of Constanta, Constanta, Romania; 3Pathology Department, “Sf. Apostol Andrei” Emergency Clinical County Hospital of Constanta, Constanta, Romania; 4CEDMOG Center, “Ovidius” University of Constanta, Constanta, Romania; 5Faculty of Law and Administrative Science, “Ovidius” University of Constanta, Constanta, Romania; 6Department of Cardio-Thoracic Pathology, “Carol Davila” University of Medicine and Pharmacy, Bucharest, Romania; 7Department of Cardio-Thoracic Pathology, Institute of Pneumology “Marius Nasta”, Bucharest, Romania; 8Faculty of Medicine, ‘Ovidius’ University of Constanta, Constanta, Romania; 9 1st Pneumology Department, Clinical Hospital of Pneumophtisiology, Constanta, RomaniaCorrespondence: Anca-Florentina Mitroi, Pathology Department, “Sf. Apostol Andrei” Emergency Clinical County Hospital of Constanta, 145 Tomis Blv, Constanta, Romania, Email anca.mitroi@365.univ-ovidius.roPurpose: The severity of COVID-19 infections varies among individuals, prompting research into factors that may influence outcomes. Numerous studies have investigated the conditions that influence the intensity of illness caused by COVID-19. These factors include the Interferon-Induced Transmembrane Protein 3 (IFITM3) rs12252 polymorphism. We investigate whether the polymorphism rs12252 plays a role within our population and observe the differences in other parameters between the mild and severe forms of the disease.Patients and Methods: The observational study examining the IFTIM3 rs12252 polymorphism based on the level of COVID-19 severity and differences between inflammatory markers. The study included 51 participants, with 31 severe and 20 mild cases.Results: The average age of participants was 54 years, and 16.1% of patients with severe symptoms were diagnosed with the AG genotype. Patients showing serious symptoms had significantly higher ESR, CRP, Fibrinogen, LDH, and D-dimer levels than those with mild symptoms.Conclusion: This study discovered a notable correlation between the G allele of IFITM3 rs12252, inflammatory markers, CT scan score, and COVID-19 severity.Keywords: COVID-19, IFITM3 protein, inflammatory markers, genotype